2016
DOI: 10.4028/www.scientific.net/msf.858.643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxide Processing on the Defects at the SiC-SiO<sub>2</sub> Interface Measured by Electrically Detected Magnetic Resonance

Abstract: Anneals in nitrogen (N) containing atmosphere have been proven as efficient means of improving the channel mobility of SiC MOSFETs. It has been demonstrated that simultaneously the density of interface traps is reduced. However, this process is not yet fully understood. In this study we show a comparison of MOSFETs annealed in different atmospheres and compare their electrically detected magnetic resonance (EDMR) spectra with electrical parameters. We find hints for the N incorporation not only passivating but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The axial C dangling bonds have the opposite anisotropy with g B c < g B⊥c and a HF splitting of a C = 80 G. No HF pair near ±40 G from the center line was observed in this work or in related studies. 23,24 As discussed above, the absence of the axial C dangling bonds is expected due to the bonding structure of the Si-face 4H-SiC/SiO 2 , which is shown in Fig. 2.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The axial C dangling bonds have the opposite anisotropy with g B c < g B⊥c and a HF splitting of a C = 80 G. No HF pair near ±40 G from the center line was observed in this work or in related studies. 23,24 As discussed above, the absence of the axial C dangling bonds is expected due to the bonding structure of the Si-face 4H-SiC/SiO 2 , which is shown in Fig. 2.…”
Section: Discussionmentioning
confidence: 87%
“…The device was compared to identically processed devices with different POA atmospheres in previous studies. 5,23 It was concluded that this device contains the same dominant EDMR active interface defect as identically processed devices that received POAs in a N-containing atmospheres. 23 The second device is a MOSFET with a thermally grown oxide.…”
Section: A Sample Descriptionmentioning
confidence: 92%
See 3 more Smart Citations